Introduction to 3D Game Engine Design Using DirectX 9 and C# - Harrison, Lynn Thomas (Apress, 2012)
The book that I could never find was one on game engine design. I wanted an object-oriented, reusable package of software that was not tightly integrated to one particular game. I knew that I wasn’t the only person interested in game engine design. I decided that, as I learned C# and managed DirectX 9 and ported my game engine to this new technology, I would document the process. The fact that you are reading this indicates you share my interest in 3D game engines.